Stability and rheological behavior of coconut oil-in-water emulsions formed by biopolymers - Gulão,Eliana da Silva (2018)
Abstract Proteins are frequently used as emulsifiers and stabilizers. In this work, two proteins with different isoelectric points were used: lactoferrin and ovalbumin. Solutions containing different proteins ratios, with different pH values, were stored for 7 days at 25 °C to analyze the system stability. Systems containing 3% w/v lactoferrin remained stable at all pH values studied, while systems containing 1% w/v ovalbumin remained stable only at a high pH value (8.0). Emulsions containing a mixture of proteins remained stable at a pH between the isoelectric points of the two proteins, which was attributed to an electrostatic bond because of the opposite charges of proteins at this pH. During the analysis of rheological properties, it was possible to observe a non-Newtonian behavior of the emulsions, using the models of Carreau and Cross to describe the pseudoplastic behavior of suspensions. This study provides important information for the use of functional ingredients.